Investigating the effect of emotion-oriented couple counseling on the threatened self-image of couples - Reisi Sarteshneizy , Mojtabah; Reisi Sarteshneizy , Ameneh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to investigate the effect of emotion-oriented couple counseling on threatened self-image. Method: The method of this research was semi-experimental and pre-test-post-test type with a control group. The statistical population of this research included couples who referred to the family culture center and counseling centers in Isfahan city. To select the desired sample, 40 couples (80 people) were selected as volunteers and randomly divided into two experimental and control groups (20 couples in the experimental group and 20 couples in the control group). The research tool was the threatened self-image from the NI-90 questionnaire. The independent variable was emotion-oriented couple counseling, which was applied to the experimental group in 10 sessions. Results: The results of covariance analysis showed that emotion-oriented couple counseling had an effect on the threatened self-image, but it had no effect on the dimensions of hope, distortion of reality, departure to a feeling of harmony, and the threatened self variable. Conclusion: it can be concluded that emotion-oriented couple counseling reduces the self-threatening image of couples.